Hepatotoxic Effects of Biosynthesized Zinc Oxide Nanoparticles and Bulk ZnO: Protective Role of Allium sativum Extract in Male Albino Rats - Hwaidi, Malak Fadil; Shaimaa Hussein Ali; Sura A. Awadh (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Zinc oxide nanoparticles (ZnO NPs) exhibit heightened surface reactivity, raising hepatotoxicity concerns driven by oxidative stress and apoptosis. Green synthesis using Allium sativum (garlic) extract is an eco-friendly alternative, yet a critical gap persists: the extract’s independent biological role remains unexamined. This study comparatively evaluated the hepatic toxicity of bulk zinc oxide (Bulk ZnO) and garlic-synthesized nanoparticles, while isolating the independent biological effect of the botanical extract. The inclusion of an extract-only group is a key novelty of this study, allowing for the differentiation between the intrinsic toxicity of the nanoparticles and the potential protective effects of the synthesis medium. Methods: Nanoparticles were biosynthesized and characterized. Eighty male albino rats were divided into eight groups (n=10) receiving oral administration for 28 days: control, extract alone, bulk zinc oxide (400, 200, 100 mg/kg), and nanoparticles (400, 200, 100 mg/kg). Hepatic enzymes, oxidative stress, and apoptotic markers were quantified. Results: Nanoparticles induced dose-dependent hepatotoxicity significantly exceeding that of bulk equivalents. The highest elevation of oxidative stress parameters, including MDA, and the lowest SOD occurred in the highest nanoparticle dose group, accompanied by exclusive mortalities. Furthermore, hepatic injury markers (ALT, AST, ALP, and bilirubin) were significantly elevated in this group. Specifically, ALT increased to a maximum of 75.74 ± 0.33 IU/L and AST to 82.23 ± 1.86 IU/L in the high-dose nanoparticle group. Conversely, the botanical extract-alone group displayed a highly favorable profile, with reduced caspase-3 and caspase-9 and improved antioxidant capacity. Conclusion: The observed hepatotoxicity is driven by the nanoparticulate form, not the synthesis medium. The extract independently conferred hepatoprotection. Rigorous preclinical safety evaluations of green-synthesized nanomaterials are imperative before biomedical application.